Cohort component population estimates for Ireland, 1911-1920: A new county-level dataset for use in historical demography - Christopher L. Colvin; Eoin McLaughlin; Kyle J. J. Richmond (Queen's University Centre for Economic History (QUCEH), 2021)
This is a dataset of vital statistics and cohort component population estimates at a spatially-disaggregated level for the island of Ireland for the period 1911-1920. The raw data were digitised by the authors using official UK government statistics. The population estimates were then derived by the cohort component method. These data provide novel intercensal population estimates at the county level that will be beneficial for researchers working in historical demography, as well as in economic and social history. The data provided can be readily reused and extended by other researchers to produce further series and indicators. An example application of the data in this manner can be seen in Colvin and McLaughlin (2021), which combines the population estimates discussed here with mortality statistics from the Spanish flu pandemic in order to demonstrate how demographic composition affects the interpretation of data on public health crises.
Keywords: J11; N33; N34; 330; Demography; historical demography; population studies; population estimates; vital statistics; mortality; migration; Ireland; twentieth century